GAMBARAN PROTEINURIA PADA IBU HAMIL TRIMESTER III DI RUMAH SAKIT KOTA PALEMBANG TAHUN 2019 - Desty Mutiara Rezky; Diah Navianti; Nurhayati (Journal of Indonesian Medical Laboratory and Science, 2020)
Preeclampsia is a disorder in pregnancy. Preeclampsia is the presence of hypertension accompanied by oedema due to pregnancy and the most important sign is the presence of proteinuria. Proteinuria occurs later in the early pregnancy until it finally appears at the end of the trimester of pregnancy. This study was aimed to describe the proteinuria of third trimester pregnant women at Hospital Palembang in 2019 based on age, gravida status, occupation, history of hypertension and weight gain during pregnancy. It was a descriptive research with approach cross sectional. The research sample consisted of 65 third trimester pregnant women taken by accidental sampling technique. Proteinuria was examined with a dipstick method that is read with a verify U120 urine analyzer. The results showed 23.1% of samples were positive one and 7.7% positive two; A high percentage of protein in urine occurred in pregnant women based on risky age <20 atau ?35 (36,4%), based on gravida status in primigravida (53,6%), based on occupation in house wife category (37,5%), based on history of hypertension with there history of hypertension before pregnant (100%), based on weight gain of obese category (50%). It is recommended for pregnant women to do a complete urine examination every time they do a laboratory examination.